The impact of Bacille Calmette-Guérin shortage on immunisation practice and policies in Europe – A Paediatric Tuberculosis Network European Trials Group (ptbnet) survey. (December 2016) - ,; Blázquez, Daniel; Bogyi, Matthias; Buonsenso, Danilo; Dreesman, Alexandra; Krivec, Uros; Mouchet, Françoise; Nejat, Sahar; Neth, Olaf; Pavić, Ivan; Ruga, Ezia; Schlags, Rupert; et al.
Summary: Background: Recent reports indicate an ongoing BCG shortage that may influence immunisation practice. This study aimed to determine current availability of BCG vaccine across Europe, and implications on immunisation practices and policies in Europe. Methods: Web-based survey among Paediatric Tuberculosis Network European Trials Group (ptbnet) members, between May and October 2015. Results: Twenty individuals from 13 European countries participated. Ongoing shortages were reported in eight countries routinely using BCG (8/11, 73%). As a consequence of the shortage, BCG was not given as completely unavailable in some countries (2/8, 25%), was given only whenever available (1/8, 13%), or only in certain regions of the country (1/8, 13%). Strategies reported to reduce loss of immunisation were administration to selected high-risk individuals (2/8, 25%), or cohorting vaccinees on specific days to maximise the use of multi-dose vials (3/8, 38%). Authorities in two countries each were considering a change of manufacturer/supplier (2/8, 25%). Conclusions: The BCG shortage in Europe leads to significant changes in immunisation policies including changes of BCG vaccine strain and manufacturer. In addition, infants and children eligible for immunisation are at risk of not receiving BCG. To ensure necessary BCG immunisations, collaboration between national health agencies and vaccine manufacturers is crucial.